FE Analyses of Corrosion-Damaged RC Beams Strengthened with FRP Components - Darwish, Omar; Roshan, Akash (My University, 2022)
Concrete is one of the most common construction materials used worldwide. The service life of concrete structures is typically limited by deterioration due to corrosion of reinforcement. Therefore, the need for strengthening corrosion-damaged structures has increased in the last decades. Strengthening using Fibre Reinforced Polymers (FRP) is one among many methods that can restore the strength and extend the service life of sound Reinforced Concrete (RC) structures. The effect of FRP strengthening on corrosion-damaged RC structures raised increased research efforts the latest years. The effectiveness of this method on strengthening and repair of corrosion damaged RC beams was studied in this thesis. The flexural behavior of two beam geometries with several variations of the strengthening system was investigated using non-linear finite element analyses (NLFEA). Corrosion damages were modelled along the whole tensile bars and a horizontal corrosion-induced crack was modelled at the level of the tensile bars along the whole width and the length of the beams. Three FRP components were used for strengthening: FRP plate, inclined U-jackets, and vertical U-jackets with the same FRP arrangement chosen for the studied beam geometries. It was found that the addition of FRP plate to the beam soffit was effective to increase the load-bearing capacity of the beams significantly. When the inclined U-jackets were added to the beams along with the FRP plate, the failure at the FRP plate end close to the supports was prevented, and some additional load-bearing capacity was obtained. However, the increase in load-bearing capacity varied due to factors such as the beam geometry as well as the arrangement, inclination, and dimension of the inclined U-jackets. The addition of vertical U-jackets did not improve the flexural behaviour of the beams when they were placed in the mid-span region. Although, the addition of the vertical U-jackets close to the supports at the location of the failure, resulted in an increase in load-bearing capacity. Furthermore, the effect of including the horizontal corrosion-induced crack in modelling of one of the beam geometries was investigated. No significant influence was observed in the flexural behaviour, except for the beam strengthened with just the FRP plate. From the results of this analysis, it was shown that the presence of the horizontal corrosion-induced crack provoked delamination failure. To further study the effectiveness of FRP strengthening, different FRP arrangement on different beam geometries need to be investigated. Moreover, it would be of interest to study their effectiveness of this method on different RC elements such as slabs and continuous beams.